2005
DOI: 10.2214/ajr.184.6.01841788
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Unenhanced Doppler Sonography in the Evaluation of Solid Breast Lesions

Abstract: Del cura et al studied the doppler parameters in solid breast lesions and based on that postulated that doppler alone was not a good modality in determining malingancy of a lesion. However the detection of null or reversed diastolic flow on spectral Doppler imaging is an infrequent but highly consistent finding in malignant lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
48
2
3

Year Published

2006
2006
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(58 citation statements)
references
References 17 publications
5
48
2
3
Order By: Relevance
“…The one case in the present study with PI greater than 4 was found to be malignant. There is overlap between the value ranges of RI in benign and malignant groups, in the present study, similar to that of delCura et al 12 The efficacy of RI in diagnosing malignancy is assessed in the present study; when a value of RI equal to or greater than 0.8, as suggested by del Cura et al 12 is used to differentiate malignant tumours from benign ones, the following statistical figures are obtained -sensitivity (38.9%), specificity (100%), positive predictive value (100%) and negative predictive value (37.1.6%); the article by del Cura et al had not mentioned using ROC analysis and likelihood ratio. It is obvious that the sensitivity is unacceptably low and this cutoff value cannot be used in Doppler studies, which are used as as screening tools.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The one case in the present study with PI greater than 4 was found to be malignant. There is overlap between the value ranges of RI in benign and malignant groups, in the present study, similar to that of delCura et al 12 The efficacy of RI in diagnosing malignancy is assessed in the present study; when a value of RI equal to or greater than 0.8, as suggested by del Cura et al 12 is used to differentiate malignant tumours from benign ones, the following statistical figures are obtained -sensitivity (38.9%), specificity (100%), positive predictive value (100%) and negative predictive value (37.1.6%); the article by del Cura et al had not mentioned using ROC analysis and likelihood ratio. It is obvious that the sensitivity is unacceptably low and this cutoff value cannot be used in Doppler studies, which are used as as screening tools.…”
Section: Discussionsupporting
confidence: 90%
“…All these parameters are excellent for a 'screening test'with high sensitivity and this study proposes a cut-off value of 0.66 for RI for the purpose of selecting cases that need biopsy (the gold standard). The article by delCura et al 12 suggesting a cut-off RI value of 0.8 has not mentioned about having carried out ROC analysis. An RI, equal to or greater than one, had poor sensitivity (8.3%) and negative predictive value (28.3%) but very high specificity (100%) and positive predictive value (100%).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[39][40][41][42][43][44] The same approach proved useful in the current study for the differentiation between benign and malignant focal pancreatic masses, with very good specificity (88.2%) and PPV (92%). However, this approach has certain limitations because several measurements were done inside the intratumoral vessels after contrast-enhancement with SonoVue, with the highest value recorded, with previous data showing large intraobserver variability between measured indices.…”
Section: Discussionmentioning
confidence: 57%
“…Color Doppler Ultrasonography is very useful in the differentiation between benign and malignant breast masses.The criteria that the presence of intratumoral or peripheral blood flow on Color Doppler indicated the existence of malignant disease and the absence of such flow in benign disease yielded promising results in early research. However, the detection of vessels on the inside of a breast nodule is significantly linked with malignancy 5 .Evaluation of the spatial distribution of vessels and ability to resolve spectral analysis may add valuable information to the imaging based diagnostic work-up of indeterminate Solid breast lesions. Breast malignancies have higher resistance indices assessed by color-coded Doppler ultrasound than benign lesions6.Choi et al 1 also attempted to evaluate the significance of resistive index (RI) in differentiating between benign and malignant breast lesions on Color Doppler Examination.…”
Section: Introductionmentioning
confidence: 99%